A simplified approach for generation of bearing curve by velocity distribution and press validation for aluminum extruded profile - Viswanath Ammu, V. N. S. U.; Mahendiran, P.; Agnihotri, Anupam; Ambade, Samrat; Dungore, P. R. (International journal of advanced manufacturing technology, 2018)
In aluminum extrusion, presence of friction at container-billet interface largely contributes to the velocity gradient during flow of metal through the container. This normally results in bending or twisting of the profile. In order to achieve the desired product quality, control of metal flow across different regions of the profile is mandatory. In extrusion die design, bearing curves are used to impart friction drag at selective areas in the die. However, various empirical formulas have been developed and used for design automation. These formulas have variables and constants which need to be ascertained accurately through design and experiments and are subject to the understanding and perception of the designers. This paper presents a simplified approach based on simulation technique for generating bearing curve of an unsymmetrical profile. For the simulation studies, the process parameters were deliberated from industrial practice. In the first iteration, a constant bearing length was used throughout the profile and it was observed that the velocity varied from 144 to 36 mm/s whereas the average velocity calculated was about 103 mm/s. Hence, in the subsequent iterations, bearing lengths were varied using systematic iterative method to achieve uniform velocities and temperature distributions of the profile at die exit. This procedure was used for generating bearing curve of the unsymmetrical profile, and it was found to be simple and efficient. To validate this approach, a die was fabricated based on the generated bearing curve data and subsequently a press trial was conducted on an extrusion press of 450 ton capacity using AA6063 alloy. Extruded profile at the die exit indicated straightness, and no bending/warping was observed during the extrusion process. The output parameters from simulation studies, i.e., extrusion load and temperature were in good correlation with the press trials confirming the validity of the method used.